Minimum Package of Public Health Services: The Adoption of Core Services in Local Public Health Agencies in Colorado - Lampe, Sarah (Am J Public Health, 2015)
Objectives. We examined the effect of a state law in Colorado that required local public health agencies to deliver a minimum package of public health services. Methods. We used a longitudinal, pre–post study design, with baseline data collected in 2011 and follow-up data collected in 2013. We conducted means testing to analyze the change in service delivery and activities. We conducted linear regression to test for system structure effects on the implementation of core services. Results. We observed statistically significant increases in several service areas within communicable disease, prevention and population health promotion, and environmental health. In addition to service and program areas, specific activities had significant increases. The significant activity increases were all in population- and systems-based services. Conclusions. This project provided insight into the likely effect of national adoption of a minimum package as recommended by the Institute of Medicine. The implementation of a minimum package showed significant changes in service delivery, with specific service delivery measurement over a short period of time. Our research sets up a research framework to further explore core service delivery measure development.